Internal Audit Performance and Corporate Governance Quality - Hadi Al-Zabari, Salim Awad; Hussein Al-Fatlawi, Ali Kadhim (Opción, 2019)
The purpose of this study is to evaluate the association of enterprise risk management and quality of corporate governance. In this aspect, the internal audit performance has been analyzed as the mediating force in the organiza- tions. The problem of this study identified from the fact that corporate governance in Iraq is diagnosed with symptoms of health hazards in areas of laws. Yet, enterprise systems proved its benefits in Iraqi firms. Therefore, the aim of this research is to examine this association. The population covers all firm listed on Amman stock exchange, the sample consists of 168 firms, they have been chosen based on being listed and based on the existen- ce of enterprise risk management system. The respondents are risk manage- ment specialists and internal auditors. Structural equation model is used for the statistical analysis. The results reveal a direct positive relationship between the enterprise risk management and the corporate governance quality. It also reveals the partial mediating effect of the internal audit performance, since the relationships become stronger and more justified. The findings highlight that organizations require implementing different practice for effectively allocating resources in adopting enterprise risk management. It also emphasized on that the firms should take into conside- ration human factors of usability and necessity of training before the adop- tion. Besides, it is considered as a first international study examine the relations (mediating effect of internal audit performance) in this frame.